Relationships among perceived quality of healthcare services, satisfaction and behavioural intentions of international students in Kuala Lumpur, Malaysia: a cross-sectional study - Aljaberi, Musheer Abdulwahid; Juni, Muhamad Hanafiah; Al-Maqtari, Rasheed Addulsalam; Lye, Munn Sann; Saeed, Murad Abdu; Al-Dubai, Sami Abdo Radman; Kadir Shahar, Hayati (BMJ Publishing Group, 2018)
OBJECTIVE: The current study aimed to investigate the relationships among the perceived quality of healthcare services, satisfaction and behavioural intentions among international students in Kuala Lumpur, Malaysia. SETTING: A cross-sectional study on public universities in Kuala Lumpur, Malaysia. PARTICIPANTS: All participants in this study were international students joining public universities in Kuala Lumpur, Malaysia. PRIMARY INDEPENDENT VARIABLE: Perceived quality of healthcare services measured on a SERVQUAL scale. PRIMARY DEPENDENT VARIABLE: Participants' satisfaction of healthcare services assessed using five items. SECONDARY DEPENDENT VARIABLE: Behavioural intentions measured on six items. RESULTS: Of the 556 international students, 500 (90%) completed the survey. The study used structural equation modelling (SEM) through the AMOS (Analysis of Moment Structures) software to analyse the data. SEM analyses showed that the perceived quality of healthcare services significantly and directly affected satisfaction, with a value of 89% and an effect size of 0.78. It also had a significant indirect impact on the behavioural intentions (0.78) of international students. The results indicated that participants' satisfaction had a statistically significant impact on their behavioural intentions (0.77). CONCLUSION: Perceived quality of care is an important driver of international students' satisfaction and their behavioural intention with healthcare services. Such relations of effects among the three investigated factors were also positive and significant.